Estimasi Arah Robot Pembersih Panel surya Menggunakan Algoritma Line Detection Klasik - Wibowo, Sapto; Athifah, Rula; Siradjuddin, Indrazno; Putri, Ratna Ika (Politeknik Negeri Malang, 2024)
Currently, solar panels are widely used in homes, offices, and buildings. Solar energy is converted into electrical energy by solar panels. The surface of solar panels determines how efficient they are; if the surface is dirty, the efficiency of solar panels will decrease. Therefore, they must be cleaned to maintain their effectiveness. Cleaning solar panels is one of the tasks that can be performed by an autonomous robot, which can move without the need for human control or remote control usage. To make the robot move autonomously, a camera is used to capture images of solar panels so that the robot can move on its own. The images captured by the camera will then be processed using a classic line detection algorithm (Hough line transform) to estimate the direction, in the form of the angle (theta), of the robot relative to the solar panel based on the lines detected by the algorithm. The direction of the robot relative to the solar panel determines the robot's future movement. The algorithm used (Hough line transform) has been able to estimate the direction of the robot quite well with a relatively fast processing time. Thus, it can be concluded that this research successfully determines the direction based on the available images